The Effect of Emotional Narratives on Instagram Reels on Student Enrollment Interest with Audience Engagement as a Mediator - Mahirohqudsi, Irma An-Nisa’; Jannah, Miftakhul Nur; Mujahidin, Muhamad Burhan; Firdaus, Maulana Abiyyu Nur; Najitama, Muhammad Fikria (Management of Education: Jurnal Manajemen Pendidikan Islam, 2025)
Schools increasingly use Instagram Reels as a promotional medium to build emotional closeness with prospective students. Researchers believe emotional narratives increase enrollment interest, but audience engagement plays a key role in mediating this effect. This study used a quantitative survey method on 141 students at SMKN 1 Ponorogo. The instrument consisted of a 4-point Likert scale questionnaire, tested for validity and reliability using SmartPLS 3.0. Researchers analyzed data using PLS-SEM to examine direct, indirect, and mediating effects. The results showed that emotional narratives significantly influenced audience engagement (β = 0.647; p = 0.000), and audience engagement significantly influenced registration interest (β = 0.594; p = 0.000). The direct effect of emotional narratives on registration interest is positive but insignificant (β = 0.166; p = 0.121). This study found a full mediating effect with a significant indirect influence (β = 0.384; p = 0.000). The R² values of 0.418 for audience engagement and 0.508 for enrollment interest indicate a moderate contribution of the model. These findings confirm that emotional narratives are compelling only when accompanied by strategies encouraging active audience interaction, increasing the likelihood of prospective students enrolling.